10Be and 9Be isotopes composition of Mn nodule 44 TKD and Mn crust 40 TKD retrieved in the South China sea during expedition SO23/2 (R/V Sonne) - Augusto Mangini; M Segl; Hermann-Rudolph Kudrass; Michael Wiedicke; G Bonani; Hans J Hofmann; Elvezio Morenzoni; Marzio Nessi; M Suter; W Wölfli (PANGAEA, 2023)
During the campaign SO23/2 (R/V Sonne) in the South China sea various manganese deposits were retrieved by dredging. Two representative samples were selected for chemical analysis: one Mn crust (0.4 cm thick) attached to a vesicular olivine basalt fragment for station 40KD and one irregular spheroidal shaped Mn nodule with rough surface and a Miocene chalk core for station 44KD. Their chemical composition was determined by X-ray fluorescence analysis on the grounded bulk sample.